Copy number variation analysis in the context of electronic medical records and large-scale genomics consortium efforts - Connolly, John J.; Glessner, Joseph T.; Almoguera, Berta; Crosslin, David R.; Jarvik, Gail P.; Sleiman, Patrick; Hakonarson, Hakon (Frontiers in Genetics, 2014)
The goal of this paper is to review recent research on copy number variations (CNVs) and their association with complex and rare diseases. In the latter part of this paper, we focus on how large biorepositories such as the electronic medical record and genomics (eMERGE) consortium may be best leveraged to systematically mine for potentially pathogenic CNVs, and we end with a discussion of how such variants might be reported back for inclusion in electronic medical records as part of medical history.